Acute Myocardial Infarction in a Child with Systemic Lupus Erythematosus and Antiphospholipid Syndrome - Zoilo Morel Ayala,; Rogelio Martínez,; Samara Mendieta,; Eduardo Benadón,; Enrique Faugier,; María del Rocío Maldonado-Velázquez, (Archives of Rheumatology, 2009)
Systemic lupus erythematosus (SLE) is a chronic, autoimmune, complex, multi-organic and episodic disease. Approximately 15% of all cases experience onset in childhood and adolescence. The coronary pathology has been recognized as the primary cause of morbidity and mortality in patients with SLE, with an incidence 9 times higher and an attributed mortality of up to 36%. Different mechanisms, alone or combined, have been implicated in the pathogenesis of coronary disease in patients with SLE. The procoagulant state in SLE patients promotes the development of acute coronary events, determined not only by the antiphospholipid antibodies, but also by the high levels of fibrinogen and plasminogen inhibitor-1. The antiphospholipid syndrome (APS) is characterized by vascular thrombosis, pregnancy loss, and thrombocytopenia with antiphospholipid antibodies. The cardiac system is one of the primary targets in APS. Patients with SLE and APS have an increase risk of acute myocardial infarction (10 times greater). Prospective studies have demonstrated the association between antiphospholipid antibodies and the first episode of venous thrombosis, acute myocardial infarction and cerebral vascular accidents. We present the clinical case of a 13-year-old male with a diagnosis of SLE and secondary APS with an extensive acute myocardial infarction. In our patient, coronary alterations were not found, which correlates more to APS. It is important to remember that patients with SLE and secondary APS may develop thrombotic complications at any level, and even though thrombotic or ischemic cardiac events are unusual, they must always be considered. (Turk J Rheumatol 2009; 24: 156-8)